2020
DOI: 10.1101/2020.09.24.309716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peripheral sgp130-mediatedtrans-signaling blockade induces obesity and insulin resistance in mice via PPARα suppression

Abstract: IL-6 signaling via its receptor (IL-6R) and co-receptor (gp130) performs multiple roles in regulating metabolic homeostasis. However, gp130 is also expressed systemically in a soluble form (sgp130), which limits soluble IL-6 receptor (sIL-6R)-mediated signaling – also called trans-signaling. Here we find that transgenic peripheral sgp130-mediated trans-signaling blockade induces mature-onset obesity, while differentially affecting age-dependent behavioral determinants of energy expenditure. In youth, trans-sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Lanton et al . showed that sgp130 transgenic mice would induce obesity by suppressing PPARα [ 37 ], which is consistent with the novel phenomenon of an increased preradiation F/B ratio. However, in our study group, sgp130 transgenic mice were the most radioresistant; therefore, the substantial decrease in their post-radiation F/B ratio is a question that needs further investigation.…”
Section: Discussionsupporting
confidence: 72%
“…Lanton et al . showed that sgp130 transgenic mice would induce obesity by suppressing PPARα [ 37 ], which is consistent with the novel phenomenon of an increased preradiation F/B ratio. However, in our study group, sgp130 transgenic mice were the most radioresistant; therefore, the substantial decrease in their post-radiation F/B ratio is a question that needs further investigation.…”
Section: Discussionsupporting
confidence: 72%
“…This finding could be indicative of a compensatory anti-inflammatory mechanism to prevent overt inflammation induced by IL-6 trans-signaling [ 211 , 212 ]. Moreover, animal studies reveal that the blockade of peripheral IL-6 trans-signaling by recombinant sgp130, induces mature-onset obesity, glucose intolerance and IR [ 260 ].…”
Section: Il-6 and Il-8 In Selected Pregnancy Pathologiesmentioning
confidence: 99%